Identity Construction Portrayed from Linguistic Features on Justin Bieber’s Instagram Fan Talks - Gharizi Matiini (Indonesian Journal of EFL and Linguistics, 2022)
Being a fan is another way of gaining an identity, and the fans' identity can be analyzed from the linguistic features used in fan talks. The present study aims to identify any identities detected from the fans’ linguistic repertoires when admiring their idols. This qualitative study is conducted by collecting the fan talks in Justin Bieber fan groups on Instagram. The use of social media promotes the increasing number of fans and encourages them to declare their affection textually. The obtained data is analyzed based on three elements of linguistic units; words, themes, and concepts. After obtaining the analysis from the elements of units, the study then shapes the relevant categories constructing the fans’ identities. The result reveals that those fans are identified with sisterhoods, sympathy, and support, for their idol, Justin Bieber, and for each other. Those natures of being fans eventually compose them into dedicated and intimate fans. Furthermore, those fans are also excellent at expressing sympathy and jokes using translingual practice.  Translingual practice is also attached in the talks as those fan use varieties of English, Bahasa Indonesia, and heritage languages.